A fish prey found in the coral snake Micrurus alleni(Serpentes: Elapidae) in Costa Rica. - Solórzano, Alejandro (2005)
Micrurus alleni (Serpentes: Elapidae) in Costa Rica. The presence of a small specimen of the swamp eel Synbranchus marmoratus (84 mm total length) in the stomach contents of an adult coral snake Micrurus alleni with 692 mm total length from the Caribbean versant of Costa Rica is reported. This eel was swallowed headfirst.